PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MENGGUNAKAN MODEL PEMBELAJARAN STAD PADA MATERI BARISAN DAN DERET BILANGAN - Asmoro, Antonius Widi (JURNAL e-DuMath, 2017)
This study aims to find an effective learning strategy in teaching mathematics for grade 4 Pringsewu IX.4 Junior High School in the school year 2012/2013 by enabling students in learning activities by using STAD learning model. Expected strategies that emphasize group work is able to cultivate the spirit of student learning. Which is the subject of the study of this class action is graders IX.4 SMP Negeri 4 Pringsewu in the school year 2012/2013, while the object is learning materials sequences and series numbers are taught with STAD model. This classroom action research conducted through three cycles and at each cycle includes planning, implementation, observation and reflection. Increasing mastery of this material from the first cycle of students can be increased by 25.71% from the initial conditions, conditions in the first cycle after the action on the second cycle increased by 2.8%. While the conditions in the second cycle after the action in the third cycle increased by 8.73%. From the results of this class action, the researchers recommend the math teacher to teach the material sequence and series by using STAD learning model.